Validation of a Sensor-Based Digital Anthropometer for Standing Height: Accuracy, Reliability, and Time Efficiency - Lukman Handoko; Indri Santiasi; Didik Sukoco; Muhammad Rofiful Fathoni (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
Accurate standing-height measurement is fundamental to ergonomic assessment, informing workstation design, equipment fit, and occupational health surveillance. Manual Anthropometer, while considered a reference standard, is susceptible to operator-dependent variability, transcription errors, and procedural inefficiency. This study aimed to design, develop, and rigorously validate a sensor-based digital standing-height measurement system by comparing its performance against a calibrated manual anthropometer. A randomized crossover experimental design was employed with 50 healthy adult participants. Primary outcomes included measurement agreement assessed via Bland-Altman analysis (95% Limits of Agreement threshold: ±0.5 cm), test-retest reliability evaluated using Intraclass Correlation Coefficient (ICC 2,1), time efficiency, and user acceptance. Bland-Altman analysis revealed a negligible mean bias of [-0.1] cm with 95% LoA ranging from [-0.8] cm to [0.6] cm, confirming non-inferior accuracy. The digital system demonstrated excellent test-retest reliability (ICC = 0.90), surpassing that of the manual method (ICC = 0.75). Measurement time was reduced by 64.7% (p < 0.001; Cohen's d = 33.50). Ninety percent of participants preferred the digital system. The sensor-based digital anthropometer provides a valid, reliable, and highly efficient alternative to manual standing-height measurement, supporting its potential application in occupational health surveillance and ergonomic assessment.